THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN ENHANCING 5TH GRADE STUDENTS’ PANCASILA EDUCATION OUTCOMES - Ulma, Sabrina Ujlifatul; S.Pd., M.Pd., Nina Sofiana; S.Psi., M.Pd., Hamidaturrohmah (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2025)
High-quality human resources drive national development in the era of globalization. This research investigates the impact of project-based learning on student learning in Pancasila education among 5th-grade students at SD Al-Islam Pengkol, Jepara. Pancasila education fosters national identity and civic character, making it a crucial component of elementary school curricula. The researchers applied a quantitative, pre-experimental design using a one-group pretest–posttest method. 24 5th-grade students participated. During the intervention, students completed group projects on Pancasila-related historical events, delivered creative presentations about national heroes, and engaged in community service projects. These activities aimed to deepen their understanding of Pancasila values. The research team collected data through pretests and posttests to evaluate the impact of project-based learning. Results showed significant improvement, with mean scores increasing from 60.04 to 77.46. A paired-sample t-test revealed that the t-count (13.187) and t-table (8.518) both exceeded the null hypothesis score (8.518) at a 95% confidence level. These results clearly demonstrate that project-based learning substantially improves students’ mastery of Pancasila material and develops their character. Project-based learning stands out as an effective and powerful strategy for equipping elementary students with national values and essential skills, thereby fostering their future success.